The knowledge of Bengkulu University’s forestry students of tree diversity in their campus - WIRYONO WIRYONO; STEFFANIE NURLIANA (Nusantara Bioscience, 2011)
Abstract. Wiryono, Nurliana S. 2011. The knowledge of Bengkulu University’s forestry students of tree diversity in their campus. Nusantara Bioscience 3: 98-103. Indonesia is rich in plant diversity which has provided daily human needs for millennia. Knowledge of diverse plants and their uses is part of ecological knowledge essential for the survival of humanity. However, rapid deforestation has reduced plant diversity and caused the loss of traditional ecological knowledge. Furthermore, the increased availability of electronic entertainment has alienated young people from nature, causing further loss of ecological knowledge. The objective of this study was to know the ability of Bengkulu University's forestry students to identify trees growing in the campus by local names and their genera. Knowing the name of trees growing in our environment is an indicator of concern for biodiversity. Results showed that forestry students had low ability to identify trees by local names and even lower by genera. Second-semester students could identify fewer trees than the higher-semester students, and the knowledge was not affected by student's gender or profession of students' parents. This low appreciation of plant diversity among young generation will have negative implication for biodiversity conservation efforts. Students should be brought closer to nature by increasing outdoor education.